Effect of Saengshik Supplementation on the Gut Microbial Composition of Healthy Korean Adults: A Single-Group Pilot Study - Shin, Ji-Hee; Ahn, Yong Ju; Chung, Won-Hyong; Lim, Mi Young; Hong, Seungpyo; Kim, Joong-Hark; Park, Mi Houn; Nam, Young-Do (Frontiers in Nutrition, 2021)
Saengshik is a type of meal-replacement product or dietary supplement comprising an uncooked and dried plant-based food mixture with various health-promoting properties, such as antidiabetic, anti-dyslipidemic, antioxidant, and anticancer properties. Although these properties are considered attributable to the various bioactive components absorbed through the intestine and its remolding effect on intestinal microorganisms, the effect of Saengshik supplementation on gut microbiota profiles has not yet been studied. In this study, we investigated the effect of Saengshik administration on the composition of gut microbiota. This single-group design trial was conducted on 102 healthy men and women who received 40 g/day of Saengshik powder for 8 weeks, during which stool samples were collected at two fixed time points (baseline and the endpoint) for gut microbiota-profiling analysis. We observed a significant decrease in the α-diversity of gut microbiota after Saengshik consumption (P < 0.05), with significant changes identified in the composition of major microbial taxa, such as Bacteroidetes (P < 0.0001), Proteobacteria, Actinobacteria, and Verrucomicrobia (P < 0.0001). Notably, the gut microbial response was related to the inter-individual variability of habitual dietary intake and enterotype at baseline. To the best of our knowledge, this is the first study investigating the effects of Saengshik intake on changes in gut microbiota, with the results suggesting that individual habitual diet patterns and gut microbial shapes should be considered key aspects in Saengshik-mediated health-promotion effects.